Police Investigation Discretion Against Perpetrators of Crimes Based on Restorative - Mandala, Subianta; Suyoto , Suyoto; Dono , Agung Puspitar; Bahara , Sahaludin (Yayasan Meira Visi Persada, 2026)
The public demands that Polri investigators be more professional in their authority as investigators and in carrying out the investigation process for various criminal acts in Indonesia, this includes exercising the authority to carry out discretionary actions in realizing the concept of restorative justice . Restorative Justice is a model of approach in efforts to resolve criminal cases, which emphasizes the direct participation of perpetrators, victims and the community in the process of resolving criminal cases. The conceptual legitimacy of the authority of Polri institutions, including Polri Investigators, aims to ensure order and uphold the law and the maintenance of public peace in order to realize public security and order in the context of maintaining domestic security and achieving national goals by upholding just human rights. The core issue is: Why do Indonesian National Police investigations of criminals based on restorative justice require discretion? And what is the discretionary strategy for Indonesian National Police investigations of criminals based on restorative justice?